Seleção do sítio reprodutivo em Antilophia galeata (Aves, Pipridae) - Bruno, Dáfini Letícia (Universidade Federal de São Carlos, 2021)
The habitat contains factors that ensure the reproduction and survival of the species. Selecting nesting places with specific characteristics that differ from the rest of the available habitat defines the nest-site selection, and this is a breeding strategy used virtually by all bird species. Although Brazil contains one of the greatest bird diversities in the world, only a few species have been studied under a nest-site selection perspective. Nest-site selection studies may contribute to the comprehension on how habitat changes can affect the local populations, and reveal habitat requirements to maintain target species or populations. The Helmeted Manakin, Antilophia galeata, is a Pipridae endemic to the savanna-like Cerrado biome, being common in gallery forests, and like most tropical forest understory passerines, it poorly studied under a nest-site selection perspective. Here, we addressed nest site-selection by the identification of plant species used as nest support and by the assessment of nine environmental variables for a population of A. galeata from southeastern Brazil. Our results revealed that females strongly selected the species Miconia nervosa (Melastomatacea) as nesting plant. In addition, Mixed-effect Generalized Linear Model (GLMM) revealed the presence of nests was positively associated to canopy cover and to the presence of Jussara palms, Euterpe edulis, and number of M. nervosa individuals around nests. These results suggest that the Helmeted Manakin nests in mature and well-preserved galleries stretches and this study highlights the importance of maintaining these habitat strips for the reproduction of the species.
Nest-site selection in the Helmeted Manakin, Antilophia galeata (Pipridae)
Keywords: Aves; Região neotropical; Cerrado; Birds; Neotropics; Habitat; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS